Changes in diagnostic usefulness of the JRS scoring system in COVID-19 pneumonia by SARS-CoV-2 vaccination. Issue 10 (October 2022) - Miyashita, Naoyuki; Nakamori, Yasushi; Ogata, Makoto; Fukuda, Naoki; Yamura, Akihisa; Ishiura, Yoshihisa; Nomura, Shosaku
Abstract: Introduction: The Japanese Respiratory Society (JRS) scoring system is a useful tool for the rapid presumptive diagnosis of atypical pneumonia in non-elderly (aged <60 years) patients. A s SARS-CoV-2 vaccination progresses, COVID-19 in elderly people has markedly reduced. We investigated changes in diagnostic usefulness of the JRS scoring system in COVID-19 pneumonia between the Delta variant group (vaccination period) and non-Delta variant group (before the vaccination period). Methods: This study was conducted at five institutions and assessed a total of 1121 patients with COVID-19 pneumonia (298 had the Delta variant). During the vaccination period, the Delta variant has spread and replaced the Alfa variant. We evaluated the vaccination period as the Delta variant group. Results: Among the six parameters of the JRS scoring system, matching rates of two parameters were higher in the Delta variant group than the non-Delta variant group (pre-vaccination period): age <60 years (77.5% vs 42.2%, P < 0.0001) and no or minor comorbid illness (69.1% vs 57.8%, p = 0.0007). The sensitivity of the diagnosis of atypical pneumonia in patients with COVID-19 pneumonia was significantly higher in the Delta variant group compared with the non-Delta variant group (80.2% vs 58.3%, p < 0.0001). When the diagnostic sensitivity was analyzed for different ages, the diagnostic sensitivities for the Delta variant and non-Delta variant groups were 92.6% and 95.5% for non-elderly patients and 39.1% and 32.5% for elderly patients, respectively. Conclusions: Our results demonstrated that the JRS scoring system is a useful tool for distinguishing between COVID-19 pneumonia and bacterial pneumonia in the COVID-19 vaccination period, but not before the vaccination period.